Cinema and experience : Siegfried Kracauer, Walter Benjamin, and Theodor W. Adorno - Hansen, Miriam, 1949-2011 (Weimar and now, 2012)
Siegfried Kracauer, Walter Benjamin, and Theodor W. Adorno--affiliated through friendship, professional ties, and argument--developed an astute philosophical critique of modernity in which technological media played a key role. This book explores in depth their reflections on cinema and photography from the Weimar period up to the 1960s. Miriam Bratu Hansen brings to life an impressive archive of known and, in the case of Kracauer, less known materials and reveals surprising perspectives on canonic texts, including Benjamin's artwork essay. Her lucid analysis extrapolates from these writings the.